2008
DOI: 10.1097/ccm.0b013e318186a938
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of aquaporin-2/vasopressin2 receptor kidney expression and tubular injury after endotoxin (lipopolysaccharide) challenge*

Abstract: Objective-Sepsis-induced organ dysfunctions remain prevalent and account for >50% of intensive care unit admissions for acute renal failure with a mortality rate nearing 75%. In addition to the fact that the mechanisms underlying the pathophysiology of sepsis-related acute renal failure are unclear, the impact on septic-induced acute renal failure of either norepinephrine, a gold-standard vasopressor, and arginine vasopressin, a candidate alternative, are not well understood.Design-Randomized and controlled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…It did not assess the use of diuretics and antibiotics; sodium and free water content of infusions and diet were not informed. Diet protein content was not reported, although an overwhelming protein diet content in AKI and in sepsis may have trigged water and sodium reabsorption leading, according to experimental evidence, to an increase in urea transporters expression in the collecting ducts and to passive urea reabsorption [5]. The clinical observation of a significant increase in urea/ creatinine ratio in the hypernatremia categories in the present study may reflect these experimental data or even may represent an underresuscitation before ICU admission, in the hypernatremic group.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It did not assess the use of diuretics and antibiotics; sodium and free water content of infusions and diet were not informed. Diet protein content was not reported, although an overwhelming protein diet content in AKI and in sepsis may have trigged water and sodium reabsorption leading, according to experimental evidence, to an increase in urea transporters expression in the collecting ducts and to passive urea reabsorption [5]. The clinical observation of a significant increase in urea/ creatinine ratio in the hypernatremia categories in the present study may reflect these experimental data or even may represent an underresuscitation before ICU admission, in the hypernatremic group.…”
Section: Discussionmentioning
confidence: 93%
“…The predominance of sepsis diagnosis in hypernatremic patients has already been reported [15,35]. Sharshar et al [36] demonstrated that vasopressin deficiency develops in sepsis and contributes to water loss, and a vasopressin renal sensibility and aquaporin 2/V2 receptor dysfunction leading to an increased free water clearance and hypernatremia has been demonstrated in experimental sepsis [5].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, in a rat endotoxin model the V2 agonist desmopressin restored endotoxininduced decreases in sodium reabsorption, inner medulary osmolality and urine osmolality, while decreasing urine flow [52] , suggesting that V2 receptor stimulation plays a beneficial role. In contrast, in an animal model of sepsis which resulted in impaired renal function in the presence of vasopressin, V2 receptors appeared to mediate impaired creatinine clearance [53] . Thus, V2 receptor agonist activity appears to be involved in renal dysfunction of sepsis but the beneficial versus adverse mechanisms are incompletely elucidated.…”
Section: The Effects Of Vasopressin On Renal Functionmentioning
confidence: 90%
“…Studies have documented that endotoxemia induced by lipopolysaccharide led to diuresis, downregulation of AQP2 (37,46), and an impaired V2R/AQP2 network as well (7,16), suggesting that proinflammatory cytokines may be involved in the regulation of AQP2 and urinary concentrating defects seen in endotoxemia. IL-1␤, a key proinflammatory cytokine, is produced by macrophages, monocytes, endothelial cells, tubular epithelial cells, and mesangial cells in the kidney.…”
Section: Discussionmentioning
confidence: 99%